Discontinuous precipitation in Mg-Al alloy studied in 3-dimensions. (1st April 2023) - Robson, J.D.; Lawson, M.J.; Donoghue, J.M.; Guo, J.; Davis, A.E.
Abstract: Discontinuous precipitation (DP) is a commonly observed mechanism by which solid solutions decompose. It results from layers of precipitate and solute depleted matrix forming across a moving boundary. The morphology of the discontinuous regions can be highly complex, and the way dislocations or twins navigate such a structure during deformation is poorly understood. Only through 3-dimensional (3D) analysis can the true morphology of discontinuous precipitation be revealed. This work presents the first 3D study of DP using a novel PFIB based serial sectioning method. The material studied is AZ80, an industrially important class of Mg-Al-Zn alloy where DP is commonly observed. The structure is revealed to consist of an interconnected network of DP regions within an interconnected matrix. The width of the DP regions show strong local variations. This structure is expected to be readily penetrated by twins and dislocations. Graphical abstract: